2019
DOI: 10.1002/admi.201900496
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Optical Absorption Studies of Point Defect Kinetics and Thermodynamics in Oxide Thin Films

Abstract: The authors review the use of in situ optical absorption to probe point defect equilibria and kinetics in oxides, with particular attention to thin films and high temperature measurements evaluating changes in oxygen content. The introduction notes the impact of point defects on oxide behavior, including differences in thin films vs. bulk materials, and describes methods to evaluate point defect equilibria and kinetics; advantages of optical absorption among these methods are highlighted. Section 2 provides an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 224 publications
(268 reference statements)
0
16
0
Order By: Relevance
“…The OTR technique has recently been applied to measure kinetics and point defect concentrations in films of the fluorite-structured Ce 0.9 Pr 0. 18,21,48,49,52 Here, we will present a brief overview of the nature and origins of optical absorption and its relationship to oxygen nonstoichiometry in nondilute STF; however, for a more detailed treatment, see ref 51 or the review by Buckner et al 40 Early work focused on a dilute case: the model system SrTiO 3 with dilute Fe on Ti sites. Mossbauer spectroscopy measurements suggested that, in that system, under oxidizing conditions, Fe changes valence from Fe 3+ to Fe 4+ as oxygen is added.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OTR technique has recently been applied to measure kinetics and point defect concentrations in films of the fluorite-structured Ce 0.9 Pr 0. 18,21,48,49,52 Here, we will present a brief overview of the nature and origins of optical absorption and its relationship to oxygen nonstoichiometry in nondilute STF; however, for a more detailed treatment, see ref 51 or the review by Buckner et al 40 Early work focused on a dilute case: the model system SrTiO 3 with dilute Fe on Ti sites. Mossbauer spectroscopy measurements suggested that, in that system, under oxidizing conditions, Fe changes valence from Fe 3+ to Fe 4+ as oxygen is added.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Some aspects of these considerations have been raised in our earlier work. 24,40,48 4.2.1. Driving Forces.…”
Section: = •mentioning
confidence: 99%
“…A very promising family of methods for tracking point defects in oxides thin films are UV-visible optical characterization techniques. [4,25] As recently reviewed by Buckner et al, [26] point defects strongly modify the electronic band structure of many oxides, giving rise to unique changes of optical properties that can be tracked by optical methods. Although UV-visible techniques cannot directly probe the concentration of point defects, by measuring the evolution of the dielectric properties of the thin film by in situ Brower analysis, it is possible to indirectly achieve a quantification of the defect chemistry of the material, similar to the measurement of the electronic conductivity but without the limitation of a non-constant charge carrier mobility.…”
Section: Introductionmentioning
confidence: 99%
“…However, the deployment of strategies for increasing mass transport at the interface level is often hindered by a lack of understanding of the fundamental controlling mechanisms, which remain largely undisclosed to date. [11,16] Several techniques based on electrical conductivity relaxation, [17] weight changes, [18] electrochemical impedance spectroscopy, [19] and color changes, [20][21][22] are widely employed in order to retrieve global information on ion transport in oxides, but are insufficient for the study of local kinetics at the nanoscale. The most common technique for the investigation of ion transport properties (oxygen diffusivity-D-and surface exchange coefficient-k) is isotopic exchange depth profiling (IEDP) in combination with secondary-ion mass spectrometry (SIMS).…”
Section: Introductionmentioning
confidence: 99%